ADAM10 and ADAM17 as Biomarkers Linked to Inflammation, Metabolic Disorders and Colorectal Cancer - Magdalena Sikora-Skrabaka; Katarzyna Weronika Walkiewicz; Ewa Nowakowska-Zajdel; Dariusz Waniczek; Joanna Katarzyna Strzelczyk (Current Issues in Molecular Biology, 2022)
ADAM10 and ADAM17 have a role in inflammation and diseases associated with inflammation, such as diabetes, cardiovascular diseases (CVD) or cancer, e.g., colorectal cancer (CRC). The aim of this study was to evaluate whether ADAM10 and ADAM17 could be biomarkers of CRC. To achieve this goal, CRC tumors and a surgical margin from 72 patients with CRC were collected. The concentration of ADAM proteins was measured by the ELISA method. Results were analyzed statistically and compared with selected clinical parameters. We found that ADAM17 protein concentration in the tumor samples was higher in patients with diabetes mellitus type 2 (DMT2) (0.28 vs. 0.2 ng/µg protein; p = 0.01) and in the surgical margin was higher both in patients with coexisting DMT2 (0.22 vs. 0.16 ng/µg protein; p < 0.05) and CVD (0.21 vs. 0.13 ng/µg protein; p < 0.01). The concentration of ADAM10 was higher in the surgical margin than in the tumor (249.34 vs. 228.82 pg/µg protein), and the concentration of ADAM17 was higher in the tumor than in the margin (0.23 vs. 0.18 ng/µg protein), but results were not statistically significant. In conclusion, the results of our study indicate that ADAM10 and ADAM17 may be potential biomarkers in cancer linked with DMT2 and CVD as diseases associated with inflammation.